Clinical and immunologic implications of COVID-19 in patients with melanoma and renal cell carcinoma receiving immune checkpoint inhibitors. Issue 7 (16th July 2021) - Switzer, Benjamin; Haanen, John; Lorigan, Paul C; Puzanov, Igor; Turajlic, Samra
Abstract : The clinical and immunologic implications of the SARS-CoV-2 pandemic for patients with cancer receiving systemic anticancer therapy have introduced a multitude of clinical challenges and academic controversies. This review summarizes the current evidence, discussion points, and recommendations regarding the use of immune checkpoint inhibitors (ICIs) in patients with cancer during the SARS-CoV-2 pandemic, with a focus on patients with melanoma and renal cell carcinoma (RCC). More specifically, we summarize the theoretical concepts and available objective data regarding the relationships between ICIs and the antiviral immune response, along with recommended clinical approaches to the management of melanoma and RCC patient cohorts receiving ICIs throughout the course of the COVID-19 pandemic. Additional insights regarding the use of ICIs in the setting of current and upcoming COVID-19 vaccines and broader implications toward future pandemics are also discussed.